2012
DOI: 10.2310/8000.2011.110397
|View full text |Cite
|
Sign up to set email alerts
|

The daunting task of “clearing” the cervical spine

Abstract: The evaluation of the cervical spine in the emergency department is a common and often challenging task. We report the case of a 70-year-old female who presented intoxicated with evidence of a recent fall. A 64-slice computed tomographic (CT) scan with sagittal and coronal reconstructions revealed no acute injury. The patient was reexamined when alert and had persistent neck pain. Flexionextension static views revealed severe subluxation of C5 on C6 with jumped facets, and subsequent magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…51,52 As outlined in our PRISMA [Preferred Reporting Items for Systematic Reviews and Meta-Analyses] 53 diagram (Fig. 2), 12 studies were included in the qualitative synthesis and data extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 As outlined in our PRISMA [Preferred Reporting Items for Systematic Reviews and Meta-Analyses] 53 diagram (Fig. 2), 12 studies were included in the qualitative synthesis and data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the evidence was further reduced because of indirectness of evidence relative to our wide definition of obtunded (population), noncomparable institutional imaging protocols (intervention and comparator), and inconsistently reported and often unavailable outcomes. Publication bias was present, as there is at least one case report 51 noting neurologic change after collar clearance with a negative C-spine CT result. Moreover, across multiple institutions, we have encountered at least one case of neurologic change.…”
Section: Resultsmentioning
confidence: 99%
“…McCracken et al noted that the radiologist only reported 23% of FE to be inadequate compared with 80% found by the authors . The limitation of FE in the acute setting where muscle spasm‐limited range of motion is common has been highlighted by several case series/reports . These authors recommend FE be delayed for several days until muscle spasm has subsided, with immobilisation in the interim.…”
Section: Resultsmentioning
confidence: 99%
“…10 The limitation of FE in the acute setting where muscle spasmlimited range of motion is common has been highlighted by several case series/reports. [35][36][37] These authors recommend FE be delayed for several days until muscle spasm has subsided, with immobilisation in the interim.…”
Section: Active Flexion-extensionmentioning
confidence: 99%
“…7 The EAST guidelines emphasized difficulty in reaching a conclusion due to heterogeneity of the population and small sample sizes in the studies they reviewed and possible publication bias, with several case reports describing unstable injuries missed using CT alone. [8][9][10] This study sought to determine if a negative 64-slice CT scan alone is sufficient to clear clinically significant CS injury in high-risk obtunded (GCS < 14) blunt trauma patients admitted to the intensive care unit (ICU). If a negative 64-slice CT scan is insufficient, we sought to determine whether a negative CT combined with gross movement  4 would be sufficient.…”
Section: Introductionmentioning
confidence: 99%